Diving Into Reef Ecosystems for Land-Agriculture Solutions: Coral Microbiota Can Alleviate Salt Stress During Germination and Photosynthesis in Terrestrial Plants - Ocampo-Alvarez, Héctor; Meza-Canales, Iván D.; Mateos-Salmón, Carolina; Rios-Jara, Eduardo; Rodríguez-Zaragoza, Fabián A.; Robles-Murguía, Celia; Muñoz-Urias, Alejandro; Hernández-Herrera, Rosalba Mireya; Choix-Ley, Francisco Javier; Becerril-Espinosa, Amayaly (Frontiers in Plant Science, 2020)
From their chemical nature to their ecological interactions, coral reef ecosystems have a lot in common with highly productive terrestrial ecosystems. While plants are responsible for primary production in the terrestrial sphere, the photosynthetic endosymbionts of corals are the key producers in reef communities. Understanding how plant-microorganism mutualistic interactions increase the ecological success of the host plants has led to the development of new tools that increase crop yields and health. Likewise, other related symbiotic microorganisms provide such ecological benefits for photosynthetic endosymbionts in corals, and these mutualistic interactions may potentially provide new agricultural solutions. For instance, coral symbiotic actinobacteria have been suggested to promote and modulate the growth of photosynthetic endosymbionts that provide energy sources to the coral. To explore the potential of coral actinobacteria as plant biostimulants, we have analyzed the activity of Salinispora strains isolated from the corals Porites lobata and Porites panamensis, which were identified as Salinispora arenicola by 16S RNA sequencing. We evaluated the effects of this microorganism on the germination, plant growth, and photosynthetic response of the wild tobacco Nicotiana attenuata under a saline regime and found a protective activity of this actinobacteria on seed germination and photosynthetic performance under natural light conditions. Further insights into the possible mechanism showed an endophytic-like symbiosis between N. attenuata roots and S. arenicola and an ACC deaminase activity by S. arenicola. We discuss these findings in the context of relevant ecological and physiological responses and biotechnological potential. Overall, our results will contribute to the development of novel biotechnologies to cope with plant growth under saline stress and highlight the importance of understanding marine ecological interactions for the development of novel, strategic, and sustainable agricultural solutions.